Policy metaphors: From the tuberculosis crusade to the obesity apocalypse. (November 2016) - Vallis, Rhyll; Inayatullah, Sohail
Highlights: Metaphor frames the construction of policy problems and solutions. Metaphors naturalise and privilege worldviews, thus affecting funding and policy. Policy metaphors can result in stigmatisation and non-trivial discrimination. Food insecurity and obesity share metaphors used around tuberculosis and immigration. Abstract: In this paper we examine the conceptual and political work that metaphors do, with particular regard to how they construct problems and thus in turn limit the range of solutions. 1 Common metaphors in the United States, Canada, the United Kingdom and Australia are examined (war, disease and crime metaphors, and the economy and nation as a body) by analysing historical and modern texts about the policy issues of tuberculosis, immigration, asylum seeking, welfare, obesity and food insecurity. Through this we show that metaphors, in conjunction with discourses, may work to: naturalise and privilege certain constructions of problems; attribute blame and responsibility; support claims about the urgency and extent of required intervention (and who should deliver it, to whom and how); influence the identification and consideration of solutions by constructing the problem in particular ways; intentionally or unintentionally result in stigmatisation and non-trivial discrimination (social and workplace); and erase or highlight the role of actors, processes, social relations and systems. Vallis has developed the analysis, the bulk of the paper, and Inayatullah has articulated the theoretical links to causal layered analaysis (CLA). While there are multiple ways to use CLA, in this paper we use CLA to map a number of issues accross perspectives and frames, and to deconstruct creating the possibility for alternative futures. We do not explore alternative or preferred futures.